2023
DOI: 10.1111/his.14960
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognostic significance of polo‐like kinase‐1 (PLK1) expression in breast cancer

Abstract: AimPolo‐like kinase‐1 (PLK1) plays a crucial role in cell cycle progression, and it is considered a potential therapeutic target in many cancers. Although the role of PLK1 is well established in triple‐negative breast cancer (TNBC) as an oncogene, its role in luminal BC is still controversial. In this study, we aimed to evaluate the prognostic and predictive role of PLK1 in BC and its molecular subtypes.MethodsA large BC cohort (n = 1208) were immunohistochemically stained for PLK1. The association with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Bromodomain-containing protein 4 (BRD4) regulates gene transcription and has been implicated in breast cancer progression by promoting cell proliferation and survival [ 155 ]. Polo-like kinase 1 (PLK1) plays a crucial role in cell cycle regulation and its overexpression correlates with poor prognosis in breast cancer patients [ 156 ]. Programmed death-ligand 1 (PD-L1) expression on tumor cells enables immune evasion and is being targeted with immunotherapy in breast cancer treatment [ 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bromodomain-containing protein 4 (BRD4) regulates gene transcription and has been implicated in breast cancer progression by promoting cell proliferation and survival [ 155 ]. Polo-like kinase 1 (PLK1) plays a crucial role in cell cycle regulation and its overexpression correlates with poor prognosis in breast cancer patients [ 156 ]. Programmed death-ligand 1 (PD-L1) expression on tumor cells enables immune evasion and is being targeted with immunotherapy in breast cancer treatment [ 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the domain of LP subtype breast cancers, PLK1 could function as a potential treatment target warranting further exploration. A recent research reported a molecular subtype-dependent prognostic role of PLK1 in breast cancer 56 . High PLK1 protein expression was remarkably related to a superior prognosis in the whole breast cancer cohort as well as the luminal subtype, but linked with a poor outcome in the triple-negative breast cancer (TNBC) subtype.…”
Section: Discussionmentioning
confidence: 99%